Analisis Persepsi Masyarakat Terhadap Risiko Longsor - Amanda Syahfira Zebua; Alfret Eliasman Zalukhu; Putra Jaya Laoli; Bimawijaya Laia (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Landslides are one of the major hazards in areas with hilly topography and high rainfall, such as Nias Island. Landslide risk is influenced not only by physical environmental factors but also by community perceptions of potential hazards. This study aims to analyze community perceptions of landslide risk in Nias and identify the factors that influence these perceptions. The research employs a quantitative approach with data collection techniques through questionnaires and interviews involving 120 respondents selected randomly from landslide-prone areas. Data analysis was conducted using descriptive and inferential statistics to determine perception levels and relationships between variables. The results indicate that community perception is at a moderate level, with education, experience, and access to information significantly influencing perception levels. Additionally, local wisdom plays an important role in supporting disaster mitigation efforts. Therefore, it is necessary to enhance education, socialization, and community involvement in community-based mitigation programs to improve preparedness for landslide risks in Nias.